CINDERELLA SESSIONS: CHALLENGES AND ISSUES IN TEACHING END OF LIFE CARE TOPICS AMONG HEALTHCARE LECTURES IN UNDERGRADUATE NURSING EDUCATION. Issue Volume 4: Issue (2014)Supplement 1 (1st March 2014) - Venkatasalu, Munikumar Ramasamy; Jackson, Susan; Walsh, Anna
Abstract : Background: In the UK, 4 out of 5 nurses lack basic pre-registration education and training in end of life care. Research shows an increased anxiety, lack of clinical skills, poor coping mechanisms among nursing students to deal with death and dying situations. Nevertheless, the reasons are unknown from the perspectives of healthcare lecturers about different end of life care teaching and learning strategies and its impact on clinical learning experiences on students. Aim: To critically examine the experiences and attitudes of healthcare lecturers' on learning- teaching strategies on end of life care topics in pre-registration nursing programmes. Methods: After ethical approval, 10 'think aloud' semi structured interviews were conducted with health care lecturers who were involved in teaching end of life care topics in one University in England. Phenomenography informed framework method was used to analyse the data. Findings: Data analysis revealed 3 themes. The theme on 'hidden death' relates to the lack of explicit curricular objectives around end of life care topics results in limited exposure to death and dying topics in pre-registration programmes. Second theme on 'protecting emotions' relates to how participants deliver end of life care teaching in a shared emotional space'. Final theme on 'Cinderella sessions' relates to lack of explicit support mechanisms for dealing emotional outcomes of end of life care teaching sessions for both teachers and students. Conclusions: Health care lecturers remains 'cautious and over conscious' on managing emotive topics that often makes end of life care topics as hidden curriculum. Despite using traditional teaching methods often trusted as beneficial in teaching end of life care topics, technology enhanced end of life care teaching-learning strategies yet unproven. Further research is urgently needed to evaluate diverse end of life care teaching strategies and its impact on clinical care outcomes.